(untitled) (Nonlinear Studies, 2014)
We discuss the vital characters, including the consistency and its proof aspects, of natural mathematics which knows no error, that of computational/computer mathematics which is, in general, ever entangled with non-separable error, and that of mathematics which attempts to capture/approximate the natural mathematics and involves a combination of an erroneous numerical form and an error-free symbolic form.We then provide the scope and importance of understanding the dis- tinction among these three mathematics with stress on scientific and engineering computations which constitute the interface between the mathematical models and their engineering implementations and which pervade every moment of our daily lives.